'ALL ABOUT MY IDEAL MENTAL HEALTH SERVICE': Users, family members and experts by experience discussing a co‐designed service - Michele Rocelli; Ludovica Aquili; Paolo Giovanazzi; Andrea Puecher; Marco Maria Goglio; Elena Faccio (Wiley, 2024)
Abstract Introduction Many studies have investigated patients' understandings of how to optimise mental health services. However, only a few studies in the Italian context have involved experts by experience (EbEs), who can be ex‐users, family members of ex‐users or current service collaborators. Their role is crucial in implementing collaborative service quality assessment projects. Method The study investigated the experience of 35 EbEs,  users, and family members who carried out a 9‐month fortnightly project aimed at imagining an 'ideal service'. The facilitators of the discussion groups (two EbEs) were interviewed; written reports of each meeting were produced with relevant comments, notes and specific suggestions; and content analysis was applied. Results The most important result concerns the effectiveness of the project management method and group leadership carried out by the two EbEs. This approach allowed for complete autonomy of the work, without professional gaze or power imbalance. Also, the ideas and specific contents focused on by the two groups offer strategies to facilitate users' entry and reception in health care centres, to reduce the stigma of mental illness, to improve the centres' physical environment, to improve organisational aspects, to keep family members actively involved and to network mental health services with other territorial services. Conclusions EbEs have proven to be key figures in ensuring equity of role in the service co‐design process. This also concerns a context, the Italian one, where their role has not yet been recognised and legalised. Their contribution and ideas to improve services could be fundamental not only in mental health centres, but also in other health facilities, and could concern the entire service delivery process rather than being limited to quality assurance, according to a virtuous circle based on active participation and transformation of the role of users. Patient or Public Contribution This work resulted from close collaboration between the two EbEs who conducted the groups, users and family members, the university, and the psychiatrist in charge of the service. All of them contributed to the research. The EbEs, researchers and psychiatrist participated in the interpretation of the data and are the co‐authors of this paper.